2017
DOI: 10.1016/j.ydbio.2017.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Irx1 regulates dental outer enamel epithelial and lung alveolar type II epithelial differentiation

Abstract: The Iroquois genes (Irx) appear to regulate fundamental processes that lead to cell proliferation, differentiation, and maturation during development. In this report, the Iroquois homeobox 1 (Irx1) transcription factor was functionally disrupted using a LacZ insert and LacZ expression demonstrated stage-specific expression during embryogenesis. Irx1 is highly expressed in the brain, lung, digits, kidney, testis and developing teeth. Irx1 null mice are neonatal lethal and this lethality it due to pulmonary imma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 25 publications
1
29
1
Order By: Relevance
“…Few reports had previously indicated the role of OEE in the regulation of tooth germ size. Iroquois homeobox 1 ( Irx1 ) transcription factor was expressed preferentially in OEE, SR, and SI cells ( Supplementary Figure 5 ) and its disruption caused a delay of tooth growth in mouse ( Yu et al, 2017 ). OEE cells are known to contribute to root formation by constituting Hertwig’s epithelial root sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Few reports had previously indicated the role of OEE in the regulation of tooth germ size. Iroquois homeobox 1 ( Irx1 ) transcription factor was expressed preferentially in OEE, SR, and SI cells ( Supplementary Figure 5 ) and its disruption caused a delay of tooth growth in mouse ( Yu et al, 2017 ). OEE cells are known to contribute to root formation by constituting Hertwig’s epithelial root sheath.…”
Section: Discussionmentioning
confidence: 99%
“…Prior researchers have proved the suppressive role of miR‐544 in iroquois homeobox 1 (IRX1) gene expression in gastric cancer . IRX1 is a member of IRX family, which encodes proteins with a homeobox domain and a characteristic Iroquois domain in the C terminal region . Evidence has shown that diminution of IRX1 expression mediated by protein arginine methyltransferase 5 is capable of contributing to gastric cancer tumorigenicity and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…8 IRX1 is a member of IRX family, which encodes proteins with a homeobox domain and a characteristic Iroquois domain in the C terminal region. 9 Evidence has shown that diminution of IRX1 expression mediated by protein arginine methyltransferase 5 is capable of contributing to gastric cancer tumorigenicity and metastasis. 10 IRX1 hypomethylation has been reported to facilitate osteosarcoma metastasis through induction of chemokine (C-X-C motif) ligand 14 (CXCL14)/nuclear factor κB (NF-κB) signaling.…”
mentioning
confidence: 99%
“…It seems that the function of notch pathway components is ambiguous as they were reported either as suppressor or activator of gastric carcinoma, and their exact effect on different steps of gastric cancer pathogenesis still remains unclear [40,42,[44][45]. Iroquois homeobox 1 (IRX1) is a member of Iroquois homeobox factors family that is required for embryonic development [46]. Down-regulation of IRX1 has been reported in several cancers including gastric cancer.…”
Section: Targets Of Dnmt In Gastric Cancermentioning
confidence: 99%